Amy the puppy whisperer - Barkley, Callie (Barkley, Callie. Critter Club, 2020)
"When Amy meets the owner of a brand-new puppy at her mom's vet clinic, she agrees to help the woman train her new pet. Amy does such a great job, she starts getting calls from more puppy owners! Things go great for a while, but soon, Amy is in way over her head. She can't say no to a puppy in need and has taken on way too many clients! Amy barely has time for school or her friends in between all the puppies. Can she dig herself out of this hole before she goes barking mad?"--